Evaluation of antioxidant potential of methanolic extracts of bark and leaf of Quassia indica (Gaertn.) Nooteb - Sudha Bai R; Anusha P (International Journal of Phytomedicine, 2018)
Plants are a natural source of secondary metabolites having antioxidant property and these compounds protect cells against adverse effects of reactive oxygen species. In the present study the methanolic extracts of bark and leaf of medicinal plant - Quassia indica (Gaertn.) Nooteb. were evaluated and compared employing ABTS cation decolorization test, DPPH scavenging assay, reducing power and scavenging potency towards hydrogen peroxide, nitric oxide and super oxide. The results suggested that the bark extract has better antioxidant efficacy than leaf for all in vitro models compared. The IC50 metrics (mg/g) of bark and leaf for the assays were ABTS (bark 552.36; leaf 1917); DPPH (bark 572.30; leaf 1782.31); H2O2 (bark 566.89; leaf 1904.32); Nitric Oxide (bark 956.75; leaf 1711.74) and Superoxide (bark 235; leaf 506.68) respectively. Results of the study concluded that Q. indica is a promosing source of antioxidants and could be exploited as a safe and stable natural agent for pharmaceutical preparations.